1997
DOI: 10.1002/(sici)1097-4652(199708)172:2<137::aid-jcp1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Induction in human osteoblastic cells (SaOS2) of the early response genesfos, jun, andmyc by the amino terminal fragment (ATF) of urokinase

Abstract: Previous studies have demonstrated that overexpression of urinary plasminogen activator (uPA) in rat prostate cancer cells results in increased skeletal metastases, which are primarily of the osteoblastic variety. The osseous activation induced by the metastases appears to be mediated through the amino terminal fragment (ATF) of uPA, which lacks the catalytic domain and can act as a growth factor for osteoblasts. To explore further the mechanism of action of uPA in bone cells, we evaluated the effects of ATF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…The binding of uPA to uPAR in some cell types causes the transmission of signaling over the cell membrane leading to increased motility (40). This ligand engagement of uPAR has been reported to cause the transient activation of a variety of signaling proteins including src-family of members (37,41,42), ERK-1 and ERK-2 (36,43), FAK (44,45), fos, jun and myc (46), and rac (47). In fact, inhibitors of these pathways block the effects of uPA (40).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of uPA to uPAR in some cell types causes the transmission of signaling over the cell membrane leading to increased motility (40). This ligand engagement of uPAR has been reported to cause the transient activation of a variety of signaling proteins including src-family of members (37,41,42), ERK-1 and ERK-2 (36,43), FAK (44,45), fos, jun and myc (46), and rac (47). In fact, inhibitors of these pathways block the effects of uPA (40).…”
Section: Discussionmentioning
confidence: 99%
“…25 The ATF can signal to the osteoblast through this receptor and activate protooncogenes, such as c-fos, that may contribute to osteoblastic stimulation. 26 The residue of the uPA molecule, now termed low-molecular-weight uPA, can continue to exert proteolytic activity and may activate latent growth factors, such as transforming growth factor ␤. Therefore, this enzyme-growth factor system may contribute to the development of focal osteoblastic metastases.…”
Section: Focal Osteogenesismentioning
confidence: 99%
“…9 Signal transduction by this scuPA fragment may be mediated in part by LRP 10 and certain integrins. 11 However, there is limited information as to the mechanism by which uPA modifies gene transcription, [12][13][14][15] and our previous studies have provided reason to hypothesize that cells express additional uPA-binding proteins that possess distinct signal-transducing activities involved in cell contractility, migration, and differentiation. 9,10,16 We previously reported that uPAR forms a complex on the surface of human SMCs with nucleolin, 17 a protein that regulates the organization of nucleolar chromatin, packaging of pre-RNA, rDNA transcription, and ribosome assembly (reviewed in Tuteja and Tuteja 18 ).…”
Section: Introductionmentioning
confidence: 99%